(untitled) (Bulletin of the Institute of Chemistry and Chemical Technology, 2021)
In recent years, the arsenic content of groundwater and soil due to the mining processes and natural and/or anthropogenic sources exceeds the permissible level, leading to adverse effects on human health and the ecosystem. The paper provides the optimized condition for the arsenic removal from the aqueous media using electrocoagulation, which is no additional reagents/chemicals, in situ generation of coagulants continuously, low energy consumption. The optimal conditions were found to be as follows: pH 7, electrolyte concentration NaCl 0.5 g L-1, current density 20 mA cm-2, and operational time 20 minutes, initial concentration of arsenic 50 mg L-1. Under the optimal condition, the maximum removal efficiency was 99.6%. Generally, the experimental results showed that the removal efficiency of As(V) from the aqueous medium was higher than 95% at pH = 4-8 ranges, 90% at the electrolyte concentration in the range of 0.25 g L-1 to 0.75 g L-1 , and 96% at the current density in the range of 15 mA cm-2 - 60 mA cm-2 respectively. Considering the variation of oxidation-reduction potential and pH during the electrocoagulation and FTIR spectra of solid residue, we found that As(V) was removed through the chemical precipitation (FeAsO4) and adsorption (Fe(OH)3×HAsO42-). Усан орчноос As(V) ионы агуулгыг бууруулах электрокоагуляцийн зохистой нөхцөлийг тогтоох судалгаа Хураангуй: Сүүлийн жилүүдэд эрдэс түүхий эдийн олборлолт, арсен агуулсан эрдэс чулуулгийн өгөршилөөр гадаргын болон гүний усан дахь арсены (As) агуулга хүлцэх агууламжаас ихсэх тохиолдлууд гарч байна. Энэ судалгааны ажлаар коагулянтаа орчинд нь тасралтгүй үүсгэдэг, нэмэлт урвалж шаарддаггүй, цахилгааны зарцуулалт багатай электрокоагуляцийн аргаар усан уусмал дахь As(V)-ыг тунадасжуулах зохистой нөхцөлийг тогтоох ажлыг хийж, үр дүнг спектрофотометр, индукцийн холбоост плазм-масс спектрометр, потенциометрийн аргаар тодорхойллоо. Зохистой нөхцөлийг тодорхойлох туршилтын дүнгээс харахад, усан орчноос As(V)-ын тунадасжуулалт рН=4-8-ын утганд >95%, электролитын концентрацийн 0.25 – 0.75 г/л мужид >90%, гүйдлийн нягтын 15 – 60 мА/см2 мужид >96% бүтээмжтэй байв. Уусмалын рН 7, NaCl-ын концентраци 0.5 г/л, гүйдлийн нягт 20 мА/см2 үед 50 мг/л концентрацитай As(V)-ын зайлуулалт хамгийн их буюу 99.6% нь усан орчноос тунадасжиж байлаа. Исэлдэх ангижрах потенциал, рН-ын хугацаанаас хамаарах хамаарал, үүссэн тунадсын нил улаан туяаны спектрийн шинжилгээний үр дүнгээр, электрокоагуляциар As(V)-ын зайлуулалт нь химийн тунадасжилт (FeAsO4), адсорбц (Fe(OH)3×HAsO42-)-ийн процессоор явагддагийг тогтоолоо. Түлхүүр үг: төмөр электрод, коагулянт, адсорбц, арсенат ион